2021
DOI: 10.1371/journal.pone.0243049
|View full text |Cite
|
Sign up to set email alerts
|

“You’re still worth it”: The moral and relational context of politically motivated unfriending decisions in online networks

Abstract: Political disagreements in social media can result in removing (i.e., “unfriending”) a person from one’s online network. Given that such actions could lead to the (ideological) homogenization of networks, it is pivotal to understand the psychological processes intertwined in unfriending decisions. This requires not only addressing different types of disagreements but also analyzing them in the relational context they occur. This article proposes that political disagreements leading to drastic measures such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Viewed through this lens, politically motivated unfriending/unfollowing may represent a form of moral boundary regulation in the maintenance of social networks rather than ideological filtration (i.e., John & Gal, 2018). In a recent study, Neubaum et al (2021) found that ". .…”
Section: Politically Motivated Avoidance and Partisan Selective Exposurementioning
confidence: 99%
“…Viewed through this lens, politically motivated unfriending/unfollowing may represent a form of moral boundary regulation in the maintenance of social networks rather than ideological filtration (i.e., John & Gal, 2018). In a recent study, Neubaum et al (2021) found that ". .…”
Section: Politically Motivated Avoidance and Partisan Selective Exposurementioning
confidence: 99%
“…Arguments on online social networks (OSNs), such as Facebook and Twitter, have become a part of everyday life (Anderson et al, 2018; Neubaum et al, 2021). This is not surprising because OSNs create a space for people to easily express their opinions, which can encourage open dialog.…”
Section: Intellectual Humility and Wrongness Admissionmentioning
confidence: 99%
“…Choosing to unfriend someone online with the click of a mouse and no feedback about why can hinder the other's ability to reflect and identify what could be done differently, which are important to moral development. Neubaum et al (2021) recently published an examination of the moral dimensions of unfriending. The ease of unfriending, for example, has been tied to a degradation and discouragement of civil discourse (Baysha, 2020).…”
Section: Technology and Friendship Ethicsmentioning
confidence: 99%